PET Imaging of Neuroendocrine Neoplasms - Rahko, Anni (My University, 2024)
Positron emission tomography (PET) has a vital role in the diagnostics and therapeutics of neuroendocrine neoplasms (NEN). NEN form a diverse group of neoplasms that arise from the cells of neuroendocrine origin. The incidence of NEN is rising mainly due to improved diagnostics. PET is a nuclear imaging modality widely used in the imaging of NEN. PET imaging utilizes radiolabeled tracers that concentrate in the tumor cells more than normal organs. Today, these radiotracers are under intense investigations. The het- erogenous nature of NEN creates the need for a variety of different radiopharmaceuticals. Some radiotracers pose also economic and logistic challenges, so novel solutions are needed. In Turku PET Center, valuable investigations are being conducted regarding the PET imaging of NEN. This thesis is a literature review where the aim is to study the most used PET radiotracers and their indications in the management of NEN. Firstly, a closer look is taken into the characteristics of NEN as well as the technical principles of PET for a more thorough understanding. The full names of PET radiotracers are complex, so abbreviations are used first containing the positron emitter followed by an acronym of the molecule. In this lit- erature review, the discussed radiotracers are 68Ga-labeled somatostatin analogues (SSA), 18F-FDG, 18F-DOPA, and exendin-4. A promising newcomer in the field,18F-SiTATE, will be discussed more profoundly. 18F-SiTATE is being studied in Turku PET Center, and it could possibly replace the widely used 68Ga-DOTANOC. Radiopharmaceuticals are also used in the peptide receptor radionuclide therapy (PRRT) of NEN. According to literature, the location of the primary tumor is relevant in the determination of the most appropriate radiotracer. Radiotracers have different affinity profiles to recep- tors on cell membranes. The uptake of a radiotracer in tumor cells represents the receptor profile of the disease. NEN are most often met in the gastrointestinal tract. For well-dif- ferentiated gastrointestinal NEN, 68Ga-labeled SSA is the most suitable option whereas 18F-FDG detects poorly differentiated neuroendocrine carcinomas (NEC). PET is also needed for the evaluation of appropriate therapies for NEN patients. Regarding PRRT, 177Lu-DOTATATE is the preferred radiotracer, but 90Y-DOTATATE is also used. New radiopharmaceuticals for the diagnostics and therapeutics of NEN are under eager inves- tigations. More research is needed on the eligibility of 18F-SiTATE, but the preliminary data is promising.
Keywords: neuroendocrine neoplasms, PET-CT, somatostatin receptor imaging